Analisis Profil Pelajar Pancasila Pada Novel Ayah Karya Andrea Hirata - Maha Maha; Hernan Khaliki (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Novels are a form of literary work that contains many positive values. So you can study novels to find positive values in them and make the most of them, especially for your students. This article presents a profile of Pancasila students in the novel Aya by Andrea Hirata. The author uses the qualitative description method to describe the profiles of Pancasila students who appear in the novel that is the subject of this study. Data analysis revealed that there are six profiles of Pancasila Students in Andrea Hirata's novel The Father. The results also show that the profile of Pancasila students desired by the Indonesian education community can be explored in the novel. Because, the profile of Pancasila Students actually calls for example, which is not only conveyed by the student environment, but also contained in fictional characters such as novels.